2014
DOI: 10.1159/000358907
|View full text |Cite
|
Sign up to set email alerts
|

Longevity and Its Regulation: Centenarians and Beyond

Abstract: Regulation of longevity depends on genetic and environmental factors. According to Svanborg, a Swedish geriatrician, over the last decades human life expectancy increased as well as the age at onset of fatal diseases. Nevertheless, autopsies of centenarians revealed the presence of several severe pathologies which could have killed them much earlier. Therefore, the emphasis is on regulation of resistance dependent on the expression of genes such as Sirtuins, mTOR pathway and others controlling body resistance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Finally, there is a possibility that future efforts will enable people to live longer (Christensen, et al, 2009), perhaps even much longer, so that the age of 102 years may not represent the true “final stage” of human longevity. Whereas this theoretically may be true, we note that, as of November 2014, in the entire world, there were only estimated to be 300–450 individuals over the age of 110 (only 79 validated at that time; see (Robert and Fulop, 2014) and http://www.grg.org/Adams/E.HTM), out of >7,000,000,000 alive, so the potential for widespread lifespan attainment much beyond that is theoretical indeed.…”
Section: Discussionmentioning
confidence: 86%
“…Finally, there is a possibility that future efforts will enable people to live longer (Christensen, et al, 2009), perhaps even much longer, so that the age of 102 years may not represent the true “final stage” of human longevity. Whereas this theoretically may be true, we note that, as of November 2014, in the entire world, there were only estimated to be 300–450 individuals over the age of 110 (only 79 validated at that time; see (Robert and Fulop, 2014) and http://www.grg.org/Adams/E.HTM), out of >7,000,000,000 alive, so the potential for widespread lifespan attainment much beyond that is theoretical indeed.…”
Section: Discussionmentioning
confidence: 86%
“…The study of ''supercentenarians'' is also against such predictions (details in [8]). Only a fraction of centenarians, about 0.15% to a maximum of about 0.5% was reported to reach 110 years, mostly women [38]. Experimentation on this subject is difficult to conceive, first because of ethical reasons.…”
Section: The Maillard Reaction Life Limiting ''Illicite'' Organic Chmentioning
confidence: 99%
“…The study by Robert and Fulop found that nutritional factors play an important role in longevity, in addition, unhealthy nutrition combined with a marked sedentary life is a major cause of obesity, reaching up to 30% of our population. Obesity is a serious risk factor for many diseases (18). The diet should be rich and varied, and increase the intake of grains and fruits.…”
Section: Discussionmentioning
confidence: 99%